2016
DOI: 10.1021/acs.jpcc.6b04646
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Investigation on the Photoetching Reaction of n-Type GaAs by Scanning Electrochemical Microscopy

Abstract: The physicochemical principle of photocorrosion and photoetching is the internal photoelectric effect of semiconductors. However, the kinetic investigation of interfacial charge transfer induced by this phenomenon has been seldom reported due to its microdomain bipolarity. GaAs is a direct band gap semiconductor with high saturated electron velocity and high electron mobility. Once the photogenerated electrons on a n-type GaAs surface are removed by Fe 3+ in the solution, it will dissolve due to the residual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…For instance, Lai et al incorporated a fiber optic light source into an SECM system to investigate the kinetics of the photoetching reaction of n-GaAs in 0.5 m H 2 SO 4 . [231] Using Fe 3+ as a redox mediator to accept the photogenerated electrons, the remaining positive holes led to GaAs oxidation and dissolution. SECM approach curves showed that the current, and corresponding interfacial charge-transfer rate, was dependent on the Fe 3+ concentration and the illumination intensity as well as the tip-substrate distance.…”
Section: Secmmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Lai et al incorporated a fiber optic light source into an SECM system to investigate the kinetics of the photoetching reaction of n-GaAs in 0.5 m H 2 SO 4 . [231] Using Fe 3+ as a redox mediator to accept the photogenerated electrons, the remaining positive holes led to GaAs oxidation and dissolution. SECM approach curves showed that the current, and corresponding interfacial charge-transfer rate, was dependent on the Fe 3+ concentration and the illumination intensity as well as the tip-substrate distance.…”
Section: Secmmentioning
confidence: 99%
“…The researchers demonstrated that tuning these parameters enabled control of the photoetching rate, which could be leveraged with the SECM for electrochemical micromachining of the semiconductor surface. [231] The Bard group has reported many studies of spatially resolved photoelectrode activity enabled by light-coupled SECM. [232][233][234][235][236][237][238][239][240] They have pioneered the application of SECM as a screening technique for photoelectrocatalysts by imaging the illuminated activity of arrays of compositionally varied catalyst spots on a semiconductor [232] or varied doping of a photoelectrode (Figure 12f).…”
Section: Secmmentioning
confidence: 99%
“…线 [39] ; (B) (a) SECM研究负载于ITO基底上的卟啉在含苯醌溶液中光电转移反应机理的示意图; (b) 修饰了ZnTPP的ITO电极 在不同波长下的渐进曲线 [8] ; (C) (a) 应用SECM研究TiO2/Fe 3+ /Br − 光电体系协同作用的实验体系示意图; (b) 不同Fe 3+ 浓度溶液 中的渐进曲线 [40] ; (D) (a) SECM研究液/液界面上Ru(bipy)3 2+ 和TCNQ的光诱导电子转移反应的实验体系示意图; (b) TCNQ •− 的 瞬态光电流响应SECM结果图 [11] ; (E) (a) SECM表面诊断模式用于研究TiO2表面吸附的•OH(ads)的实验体系示意图; (b) 得到的 探针电流 [42] ; (F) (a) SECM研究n型GaAs在Fe2(SO4)3/H2SO4溶液中的光刻蚀示意图; (b) 不同光照强度下10 mM Fe 3+ 溶液中的 渐进曲线 [43] (网络版彩图)…”
Section: Secm在光电化学体系中的应用研究unclassified
“…To improve the practicality of III–V semiconductor photoanodes, a detailed understanding of the photocorrosion process is needed along with simple, cost-effective corrosion protection strategies. Researchers have studied the mechanism of GaAs photocorrosion and proposed reaction pathways that explain the different dissolution behavior of the Ga and As components in acidic vs alkaline media, as well as the formation of oxide layers on n-GaAs electrodes in neutral electrolyte. Herein, the focus is on n-GaAs photoanodic behavior in aqueous acidic electrolyte, similar to the operating media for some of the most advanced electrolyzers. Ideally, the semiconductor surface would be conformally coated in a low-cost process with a thin layer of chemically inert material which simultaneously enhances the OER kinetics.…”
Section: Introductionmentioning
confidence: 99%